Interpretações de uma crise: os debates sobre moeda e comércio na Inglaterra durante o parlamento de 1621 - Suprinyak, Carlos Eduardo (História Econômica & História de Empresas, 2014)
The parliament of 1621 witnessed extensive debating of economic issues by those engaged in finding solutions for the exacting crisis which affected England at the time. These proceedings offer the background against which some of the most relevant economic literature of the period was produced. As debates progressed, two contrasting perspectives gradually emerged. One of them argued that monetary imbalances were responsible for bullion outflows and sluggish economic activity, while the other believed that monetary flows were ultimately caused by an unfavorable balance of trade. These were exactly the same issues at stake in the controversy between Gerard de Malynes and Edward Misselden in the early 1620’s, to which Thomas Mun would provide a solution with his strict adherence to the balance of trade. Thus, through an analysis of economic debates in the parliament of 1621, this paper seeks to offer an essential element for understanding early-17th century English economic thought.